VIDEOGAME ENGINES AND THE POLITICS OF ’DEMOCRATISED’ SOFTWARE DEVELOPMENT - Nicoll, Benjamin (AoIR Selected Papers of Internet Research, 2019)
A videogame engine is a software tool that enables interactive digital content to be built, and a code framework that enables that content to run on different platforms, including consoles, smartphones, and virtual reality devices. Today, game engines form the backbone of videogame development and, increasingly, software development more broadly. The Unity engine — a key player in this industry, and the main case study of this paper — aims to ‘democratise game development’ through an accessible editing interface, a flexible licensing structure, and a toolset that is interoperable with a range of different design tools, middleware software, programming languages, and production workflows. This paper evaluates the core claim made by and about Unity — that it is has democratised game development — through a framework that analyses the engine’s ‘articulations’ in multiple areas of software culture: design, workflow, education, identity, political economy, and governance. These contexts form a ’circuit of cultural software’ wherein the discourse of democratisation functions as a governing logic. Drawing on semi-structured interviews with 24 Australian developers, students, and educators, as well as participant observation and ethnographic fieldwork, this paper argues that people feel empowered by Unity not only because of the tools it provides, but also because of its capacity to create what Angela McRobbie (2016) calls a ‘creativity dispositif’ — an affective space where developers are granted a degree of social security to explore possibilities for self-entrepreneurship in what would otherwise be a career path fraught with risk and uncertainty.